Analisis Perilaku Membolos dan Penanganannya (Studi Kasus Peserta Didik): Studi Kasus Peserta Didik di SMAN 9 Enrekang - Syamsyurahmi (INSIGHT: Jurnal Bimbingan Konseling, 2025)
This study aims to analyze truancy behavior among students at SMAN 9 Enrekang and examine the management efforts implemented by the school to reduce and prevent such behavior. This type of research uses qualitative with a case study approach. Data collection techniques are by means of observation, interviews, and documentation. The results of the study show 1). Leaving the school premises before the end of the lesson without the teacher's knowledge and without a clear reason, truancy behavior is carried out solely because of a lack of motivation to learn, characterized by drowsiness and boredom while studying. 2). Absent from school without explanation, it was found that the trigger for this behavior was waking up late causing delays in entering school so that students no longer wanted to go to school even though they still went to school even though they did not attend class. (3) The impact of truancy in terms of academics can cause failure to move up a class due to low grades, in terms of social aspects, namely pushing the subject into more negative friendships such as committing additional violations, namely smoking in hangouts while truant and playing online games (4) Efforts to handle truancy behavior by providing counseling using the Cognitive Behavior Therapy approach, cognitive reconstruction techniques.